2021
DOI: 10.3390/nu13124286
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Obligatory Exercise and Eating Attitudes, and the Mediating Role of Sociocultural Attitudes towards Appearance during the COVID-19 Pandemic

Abstract: A strong sociocultural context could affect an individual’s aesthetic standards. In order to achieve a socially recognized ideal appearance, obligatory exercisers might increase dieting behavior when exercise actions are disturbed, thereby placing the individual at risk of eating disorders. The current study mainly examined the relationship between obligatory exercise and eating attitudes during the COVID-19 pandemic, and considered the mediating role of externalized sociocultural attitudes towards appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…Although no comparative studies on obligatory exercise between Polish and Chinese young people were found, a study on the physical activity of French and Japanese adults confirmed that adult physical activity varies by gender and culture and that the global wave of Western sports and physical culture has not turned Japanese sports into an exact replica of Western sports [ 55 ]. Some studies also demonstrated that a solid sociocultural background influences obligatory exercise through body ideals [ 14 , 16 , 56 ]. The differences in obligatory exercise exhibited by young Polish and Chinese men and women in this study may be due to differences in their sociocultural attitudes toward the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no comparative studies on obligatory exercise between Polish and Chinese young people were found, a study on the physical activity of French and Japanese adults confirmed that adult physical activity varies by gender and culture and that the global wave of Western sports and physical culture has not turned Japanese sports into an exact replica of Western sports [ 55 ]. Some studies also demonstrated that a solid sociocultural background influences obligatory exercise through body ideals [ 14 , 16 , 56 ]. The differences in obligatory exercise exhibited by young Polish and Chinese men and women in this study may be due to differences in their sociocultural attitudes toward the body.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 ]. From a global public health perspective, obligatory exercise is more prominent among emerging adults aged 18 to 30 and is becoming a threat to young people’s health in Europe, Asia, and the Americas, including Poland and China [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Sociocultural factors have been shown to play a crucial role in developing obligatory exercise [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the initial version of the OEQ has some limitations regarding unidimensionality, the revised version shows that this questionnaire is justifiably multidimensional. The OEQ by itself does not have the cutoff value, but some authors used a relatively high cutoff of two standard deviations above the mean 11 or the middle of the total score 13,30 for identifying those at risk and obligatory exercisers. Further, this instrument is used for clustering groups of pathological obligatory exercisers and well-adjusted exercisers.…”
Section: Discussionmentioning
confidence: 99%
“…As in this study, other authors also confirm the findings that young men express more obligatory exercise behaviour. 13 There are different reasons why men and women engage in obligatory exercise. Pritchard and Beaver 31 state that body tone improvement, enjoyment, and attractiveness were the main reasons predicting obligatory exercise for men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation